2010
DOI: 10.1159/000281825
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chordin-Like 1 on MC3T3-E1 and Human Mesenchymal Stem Cells

Abstract: Since the discovery that bone morphogenetic proteins (BMPs) are able to induce ectopic bone formation, considerable effort has been devoted to apply it for bone regeneration. BMP activity needs to be temporally and spatially controlled and the organism has devised ways to achieve it. Here we show that the BMP inhibitor chordin-like 1 can interfere with BMP2 signalling thereby affecting the osteogenic differentiation of MC3T3-E1 cells. Besides its function as a BMP antagonist, chordin-like 1 enhanced the prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 93 publications
0
9
0
Order By: Relevance
“…We show that CHDL1 alone, or even in combination with TSG, does not modify proliferation, at difference of studies in other systems [53]. The effect of NOGGIN and both CHDL-1 and CHDL-2 on cultures of digit progenitors, concerns tissue differentiation, and becomes intensely potentiated by TSG.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…We show that CHDL1 alone, or even in combination with TSG, does not modify proliferation, at difference of studies in other systems [53]. The effect of NOGGIN and both CHDL-1 and CHDL-2 on cultures of digit progenitors, concerns tissue differentiation, and becomes intensely potentiated by TSG.…”
Section: Discussionmentioning
confidence: 69%
“…The low anti-BMP influence on gene regulation in rh-CHDL-1 alone treatments prompted us to check whether it has an effect promoting cell proliferation as reported in cultures of human mesenchymal stem cells [53]. However, no changes in cell proliferation or apoptosis were observed in cultures treated with different doses of CHDL-1 (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…Previous studies demonstrated that CHRDL1 enhanced the proliferation of MSCs [62]. IGSF10 was a unique marker of early osteochondral progenitor cells [63] and TWIST2 played a role to maintain MSCs in preosteoblast-like state [64, 65].…”
Section: Discussionmentioning
confidence: 99%
“…Follistatin is secreted by adipose tissue explants (27), and noggin is a well-established and secreted inhibitor that binds to the BMP receptors, but its biological functions are mostly undetermined (6,28). Chordin and chordin-like-1 (CHRDL1) are secreted proteins that bind BMP2, -4, and -7 (29,30), and CHRDL1 and has been shown to enhance the proliferation of human mesenchymal stem cells (31). Gremlin-1 (GREM1) is a potent extra-and intracellular inhibitor of BMP4 (32) and is involved in fibrosis and arthritis development (33).…”
mentioning
confidence: 99%